Rapid Recovery After Total Joint Arthroplasty Using General Anesthesia - Stambough, Jeffrey B.; Bloom, G. Barnes; Edwards, Paul K.; Mehaffey, Gregory R.; Barnes, C. Lowry; Mears, Simon C. (The Journal of arthroplasty, 2019)
Multiple papers have purported the superiority of spinal anesthesia used in total joint arthroplasty (TJA). However, there is a paucity of data available for modern general anesthesia (GA) regimens used at high-volume joint replacement centers. We retrospectively reviewed a series of 1527 consecutive primary TJAs (644 total hip arthroplasties and 883 total knee arthroplasties) performed over a 3-year span at a single institution that uses a contemporary GA protocol and report on the length of stay, early recovery rates, perioperative complications, and readmissions. From the elective TJAs performed using a modern GA protocol, 96.3% (n = 1471) of patients discharged on postoperative day 1, and 97.2% (n = 1482) of subjects were able to participate with physical therapy on the day of surgery. Only 6 patients (0.4%) required an intensive care unit stay postoperatively. The 90-day readmission rate over this time was 2.4% (n = 36), while the reoperation rate was 1.3% (n = 20). Neuraxial anesthesia for TJA is commonly preferred in high-volume institutions utilizing contemporary enhanced recovery pathways. Our data support the notion that the utilization of modern GA techniques that limit narcotics and certain inhalants can be successfully used in short-stay primary total joint arthroplasty. IV– Case series.